Project Management for Mobility Engineers: Principles and Case Studies - Mago, Angelo E. (Warrendale SAE International, 2020)
The book provides core project management principles adapted for engineers working in the mobility sector, including the automotive, aerospace, and related industries. Through real-world case studies, the book illustrates how engineers can apply project management techniques to achieve technical, cost, and schedule goals.
Keywords: Công nghệ kỹ thuật ô tô